Vacuum drying: a new technique for drying ornamental flowers and bracts - B, RAGHUPATHI; GANTAIT, SUBHENDU S (The Indian Journal of Agricultural Sciences, 2022)
The vacuum drying technology was standardized as a new way for drying of ornamental flowers and bracts for preparing value added dry flower products. The results of experiment concluded that embedding in silica gel and vacuum oven drying (temp. 55Â°C with 100 mmHg pressure) for 2.5 h was best suitable for drying of Wedelia trilobata flowers, 3 h was appropriate for Ixora chinensis flowers and Mussaenda erythrophylla bracts, and 5 h was found ideal for Ageratum conyzoides flowers.